Urgensi Asbab Al-Nuzul Ayat-Ayat Ahkam - Ruslan, Ruslan (Syariah: Jurnal Hukum dan Pemikiran, 2013)
One way to understand the Al-Quran guidance is using asbab al-nuzul. Fortunately, this approach is not satisfactory for some people, so they start to doubt the importance of it. After the ulum Al-Quran literature survey and also to the related laws, it was found out that it is a necessary to consider the history of Islam/ Arab society as a knowledge in using asbab al-nuzul. The combination of those two knowledge will bring to the true and scientific understanding. Based on both knowledge: the importance of ashab al-nuzul and the laws of ahkam, the knowledge that can be formulated are: knowing the wisdom of the establishment of the laws, avoiding the misunderstanding about the law materials, avoiding the presumption of the laws limitations, justifying the laws according to its purpose, and revealing the hidden statement and meaning of laws.